Atonement, Law, and Justice The Cross in Historical and Cultural Contexts - Vidu, Adonis (Grand Rapids, Michigan Baker Academic, 2014)
Adonis Vidu tackles an issue of great current debate in evangelical circles and of perennial interest in the Christian academy. He provides a critical reading of the history of major atonement theories, offering an in-depth analysis of the legal and pol
Keywords: Jesus Christ -- Crucifixion. Atonement -- History of doctrines. Law and gospel